Analysis of Isoliquiritin and Isoliquiritigenin from Insampaedoksan Fermented by Lactobacillus plantarum 144 Using RP-HPLC - Lee, K.J.; Jung, P.M.; Roh, J.H.; Ma, J.Y. (Asian Journal of Chemistry, 2014)
Insampaedoksan is a traditional herbal medicine used for antipyretic and antiinflammatory diseases. Thus isoliquiritigenin have bioactivity effects such as antioxidant, estrogenic and anticancer. The level of isoliquiritin and isoliquiritigenin in insampaedoksan were investigated before and after fermentation with Lactobacillus plantarum 144, along with isoliquiritin and isoliquiritigenin extraction efficiency with 100 % water, 60 % aqueous MeOH and 100 % MeOH. The characterization of isoliquiritin and isoliquiritigenin were achieved by comparing its retention time (tR), molecular weight and UV absorption with those of the standard compound. The extraction efficiency of isoliquiritin and isoliquiritigenin were the highest with 100 % MeOH. After fermentation, the amount of 100 % MeOH extract isoliquiritigenin was selectively increased (202.73 %) and isoliquiritin was selectively decreased (82.57 %). The bioconversion rate of isoliquiritin to isoliquritigenin was 39.93 %. Also, the molecular mass of the fermented insampaedoksan fraction (#1) were shown via LC-MS and, its high purity was shown to be above > 95 %. Thus, qualitative and quantitative analyses of isoliquiritin and isoliquiritigenin in insampaedoksan and fermented insampaedoksan were conducted.